PELATIHAN TIK (TEKNOLOGI INFORMASI DAN KOMUNIKASI) IMPLEMENTASI PENGEMBANGAN TIK BAGI GENERASI Z DAN ALPHA SISWA SD,SMP DAN SMA DI DESA GUMUKMAS KABUPATEN JEMBER - Ahmad Sauqi; Muhaimin Dimyati (STIE Mandala Jember, 2022)
Generation Z is a person born between 1995 and 2010. Generation Alpha is a person born after 2011. We predict that in the future there will be a super tight selection in the placement of workers. It is very important to develop soft skills and hard skills for the younger generation, especially Generation Z and Alpha. This service is in response to a phenomenon in society in Gumukmas Village, Jember, especially elementary, middle and high school children who are not so familiar with the use of information technology. The conclusion of this service was that they stated that after being given training they had started to get used to using computers. Starting to have an interest in exploring various software, especially those needed in the world of work. The point is that this study group already has the enthusiasm to develop science in the field of ICT because they are aware that as Generation Z and Alpha they must start getting used to being familiar with computers from an early age. Suggestions from the results of this dedication: Mastering ICT requires patience and must be continuous in learning it. Remember that learning ICT is a multilevel knowledge, so you must be patient to learn from the lowest level. Slow down and enjoy the learning process, don't be shy to ask.